2012
DOI: 10.1345/aph.1r167
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Galactogogues in the Breastfeeding Mother

Abstract: Nonpharmacologic recommendations should be exhausted before adding therapy. Although anecdotal evidence encourages the use of metoclopramide, fenugreek, asparagus, and milk thistle for their galactogogue properties, efficacy and safety data in the literature are lacking. Oxytocin and domperidone are potentially available for compounding purposes, but safety data are limited. More studies are needed to evaluate the effects of available galactogogues on breast milk production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 40 publications
1
76
0
11
Order By: Relevance
“…Despite the scarcity of clinical data on the actual increase of breast milk production, many women continue to use natural galactagogues (Forinash et al 2012;Zapantis et al 2012). Several researchers have surveyed galactagogues in different world regions, among them, Brückner (1996) in Europe, Dandotiya et al (2013) in India, Othman et al (2014) in Malaysia, Bnouham (2010) in Morocco, and Froemming (2006) and Bussman and Glen (2010) in Peru.…”
Section: Maternal Knowledge and Use Of Galactagogues In Andean Communmentioning
confidence: 99%
“…Despite the scarcity of clinical data on the actual increase of breast milk production, many women continue to use natural galactagogues (Forinash et al 2012;Zapantis et al 2012). Several researchers have surveyed galactagogues in different world regions, among them, Brückner (1996) in Europe, Dandotiya et al (2013) in India, Othman et al (2014) in Malaysia, Bnouham (2010) in Morocco, and Froemming (2006) and Bussman and Glen (2010) in Peru.…”
Section: Maternal Knowledge and Use Of Galactagogues In Andean Communmentioning
confidence: 99%
“…It has been reported that mothers with insufficient milk to feed their infants may be able to benefit from the use of galactogogues (McInnes and Chambers, 2008;Osadchy et al, 2010). Galactagogues are used when pharmacological interventions are required (Forinash et al, 2012).Traditionally the plant Guiera senegalensis has been used as a herbal galactagogue in the Western parts of Africa and according to traditional practitioners the use of this plant to enhance milk production in both human and animal species cannot be overemphasized. Domperidone is a common synthetic drug that can be used when all efforts to achieve sufficient milk production for the infant have failed (Donovan and Buchanan, 2012).This and other commonly used galactogogues in women are associated with side effects such as dry mouth syndrome or hyposalivation, gastrointestinal disorders, cardiac arrhythmia, lethargy, sedation, extrapyramidal symptoms such as hypertension, tremor, , facial seborrhea, and hyperhidrosis, and even sudden death (Tabares et al,2014).…”
Section: Introductionmentioning
confidence: 99%
“…It may be synthetic, plant-derived,or endogenous. Synthetic galactagogues such as domperidone and metoclopramide interact with the dopamine system in such a way to increase the production of prolactin (Forinash, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Galactagogues may be considered when nonpharmacologic interventions are found to be insufficient (Amir et al, (2011;Forinash, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%